In silico characterization of microRNAs-like sequences in the genome of Paracoccidioides brasiliensis - Curcio, Juliana Santana de (2019)
Eukaryotic cells have different mechanisms of post-transcriptional regulation. Among these mechanisms, microRNAs promote regulation of targets by cleavage or degradation of the mRNA. Fungi of the Paracoccidioides complex are the etiological agents of the main systemic mycosis of Latin America. These fungi present a plasticity to adapt and survive in different conditions, and the presence of microRNAs-like molecules could be part of the mechanisms that provide such plasticity. MicroRNAs produced by the host influence the progression of this mycosis in the lungs besides regulating targets involved in apoptosis in macrophage, activation of T and B cells and the production of cytokines. Therefore, this work analyzed the presence of regions in the genome of this fungus with a potential to encode microRNAs-like molecules. Here we show by analysis of sequence similarity the presence of 18 regions, putatively coding for microRNAs-like molecules in the Paracoccidioides brasiliensis genome. We also described the conservation of dicer and argonaut proteins and the cognate transcripts induced in the yeast parasitic phase. This work represents a starting point for the analysis of the presence of those molecules in the morphological stages of the fungus and their role in fungal development.